Biodegradable calcium carbonate/mesoporous silica/poly(lactic-glycolic acid) microspheres scaffolds with osteogenesis ability for bone regeneration. Issue 9 (29th January 2021) - Xu, Weikang; Zhao, Ruifang; Wu, Tingting; Li, Guixiang; Wei, Kun; Wang, Liyan
Abstract : Sintered microsphere-based scaffolds provide a porous structure and high-resolution spatial organization control, show great potential for bone regeneration, mainly from biodegradable biomaterials including poly(lactic-glycolic acid) (PLGA). Abstract : Sintered microsphere-based scaffolds provide a porous structure and high-resolution spatial organization control, show great potential for bone regeneration, mainly from biodegradable biomaterials including poly(lactic-glycolic acid) (PLGA). However, acidic monomer regeneration, mainly from biodegradable biomaterials including poly(lactic-glycolic acid) (PLGA). However, acidic monomers generated by PLGA degradation tend to cause tissue inflammation, which is the central issue of PLGA-based bone regeneration scaffolds development. In this work, calcium carbonate (CC)/hexagonal mesoporous silica (HMS)/PLGA sintered microsphere-based scaffolds were developed. The scaffolds possessed a three-dimensional (3D) network structure and 30–40% porosity. The degradation results indicated that CC/HMS/PLGA scaffolds could compensate for pH increased caused by PLGA acidic byproducts effectively. Degradation results showed that CC/HMS/PLGA scaffold could effectively compensate for the pH increase caused by PLGA acidic by-products. Composite CC additives can induce the increase of adhesive proteins in the environment, which is conducive to the adhesion of cells to scaffolds. Mesenchymal stem cells (MSCs) proliferation and osteogenic differentiation were evaluated by CCK-8 assay, alkaline phosphatase (ALP) activity, ALP staining, and Alizarin Red staining. The results showed that compared with HMS/PLGA scaffolds, the proliferation of MSCs cultured with CC/HMS/PLGA scaffolds was enhanced. When cultured on the CC/HMS/PLGA scaffolds, MSCs also showed significantly enhanced ALP activity and higher calcium secretion compared with the HMS/PLGA scaffolds. CC/HMS/PLGA sintered microsphere-based scaffolds provides an attractive strategy for bone repair and regeneration with better performance.